IMPROVING INFANT GROWTH THROUGH BABY MASSAGE: A STUDY ON 3–6-MONTH-OLD BABIES IN TAMANSARI HEALTH CENTER, TASIKMALAYA - Sri Sutiawati, Tia; Cahyati, Yanti; Putri Suptiani, Laila; Widia Lestari, Meti; Diana, Helmi (Media Informasi, 2025)
Infant weight that has not increased optimally is still a child health problem in Indonesia. One of the non-pharmacological interventions that can be given is infant massage. Infant massage has been shown to be beneficial in stimulating the nervous system and blood circulation, increasing appetite, and improving the quality of infant sleep, all of which contribute to weight gain. Purpose This study aims to determine the effect of infant massage on the weight of infants aged 3–6 months in the Tamansari Health Center, Tasikmalaya City. The method of this type of research is a quasi-experiment with a one group pretest-posttest design. Sampling was carried out using a purposive sampling technique of 20 infant respondents aged 3–6 months. The intervention in the form of infant massage was carried out for 15 minutes, once a week for 4 weeks. Data analysis using the Paired T-Test test, Results The average infant weight increased significantly. The results of the Paired T-Test test showed a p value = 0.007 in the intervention group. Conclusion Infant massage has a significant effect on increasing the weight of infants aged 3–6 months. Therefore, it is recommended for mothers to imagine regular baby massage as a form of beneficial growth and development stimulation